2022
DOI: 10.3390/sports10040058
|View full text |Cite
|
Sign up to set email alerts
|

Talent Identification in Elite Adolescent Ice Hockey Players: The Discriminant Capacity of Fitness Tests, Skating Performance and Psychological Characteristics

Abstract: Background: The process of talent identification in ice hockey occurs during middle adolescence when players are selected to participate in “off-season” evaluation camps, where coaches observe their fitness levels and status of development. Recently, the Quebec ice hockey federation opted for a holistic approach by evaluating players based on three criteria: (1) fitness, (2) skating abilities and (3) personality traits and psychological assets. This study aimed to analyze the discriminant validity of a multi-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…On the other hand, some authors have shown that height or body mass may influence the selection process during detection camps for youth hockey players [ 12 ]. Results indicate that anthropometric characteristics, such as body mass, could negatively affect ice hockey performance in female athletes [ 50 ], a hypothesis recently confirmed by Lemoyne and colleagues [ 14 ].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…On the other hand, some authors have shown that height or body mass may influence the selection process during detection camps for youth hockey players [ 12 ]. Results indicate that anthropometric characteristics, such as body mass, could negatively affect ice hockey performance in female athletes [ 50 ], a hypothesis recently confirmed by Lemoyne and colleagues [ 14 ].…”
Section: Introductionmentioning
confidence: 84%
“…Consequently, fewer differences could be observed as the overall level became more homogenous. The role of anthropometry (especially body mass) for on-ice performance has already been examined by Lemoyne et al [ 14 ], with their anthropometric model which was non-significant unlike the skating performance model. Unlike previous studies and our previous results, when data were analyzed with a sub-group classification, we observed that being taller and heavier were advantageous for on-ice performance for the female group in Camp 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations